Modulating Electron Beam–Sample Interactions in Imaging and Diffraction Modes by Dose Fractionation with Low Dose Rates. (December 2021) - Kisielowski, Christian; Specht, Petra; Rozeveld, Steven J.; Kang, Joo; Fielitz, Alyssa J.; Barton, David; Salazar, Anthony C.; Dubon, Oscar D.; Van Dyck, Dirk; Yancey, David F.
Abstract: Abstract : Technological opportunities are explored to enhance detection schemes in transmission electron microscopy (TEM) that build on the detection of single-electron scattering events across the typical spectrum of interdisciplinary applications. They range from imaging with high spatiotemporal resolution to diffraction experiments at the window to quantum mechanics, where the wave-particle dualism of single electrons is evident. At the ultimate detection limit, where isolated electrons are delivered to interact with solids, we find that the beam current dominates damage processes instead of the deposited electron charge, which can be exploited to modify electron beam-induced sample alterations. The results are explained by assuming that all electron scattering are inelastic and include phonon excitation that can hardly be distinguished from elastic electron scattering. Consequently, a coherence length and a related coherence time exist that reflect the interaction of the electron with the sample and change linearly with energy loss. Phonon excitations are of small energy (<100 meV), but they occur frequently and scale with beam current in the irradiated area, which is why we can detect their contribution to beam-induced sample alterations and damage.